Analisis Tata Kelola Dan Perencanaan Investasi Teknologi Informasi Dengan Metode Cobit Dan Val It - Yayan Hendrian (Universitas Bina Sarana Informatika, 2019)
Abstract - IT Governance and the development of appropriate information technology, aligned with business strategy and in accordance with the target is a priority, but often development projects are not expected to match the even, there are many information technology development project failure or canceled in the middle of the road. That's because information technology governance and IT investment planning are not good. It is necessary to analysis IT governenace and planning of IT investment. The selected sample is PT. Candi Malindo Bangkit with five (5) respondents involved. Tools in this study using the COBIT framework for data and opinions about IT governance and Val IT for IT investment planning. The selected domain from the COBIT framework are DS4 (continuous service), DS5 (information system security) and DS11 (data management), and the domain of Val IT are Value Governance (VG), Portfolio Management (PM) and Investment Management (IM) . Then based on the analysis can be known maturity level of IT governance and IT investment planning. The analysis shows that the current PT. Candi Malindo Bangkit still at maturity level 1 (one) or at the level of the initial/Adhoc which means IT governance and IT investment planning has been no standardization process, yet organized and implemented based on the needs of a sudden.Keywords: Audit, IT Governance, COBIT, Val IT